Review: Brewing Conventional Beer with Sorghum Cultivars (Global Journal of Medical Research, 2021)
Malting sorghum grains yield malts with enzymes which hydrolyse their innate carbohydrates, proteins and lipids. Quality of sorghum malt is influenced by steeping regimes, steep liquor constituents, temperature and duration of germination, enzymatic activities during germination and different kilning temperature regimes. Malts of different sorghum cultivars differ in their diastatic power. Different mashing regimes influence composition of sorghum wort extracts, wort viscosity and fermentability. Fermentation conditions, yeast strains and ageing influence beer character. Sorghum beers result from fermenting either wholly sorghum wort, combinations of varying percentages of sorghum and barley wort or wort from sorghum mash treated with exogenous enzymes. Sorghum beers satisfy demand of coeliac sufferers who are allergic to gluten, present in barley beers. Current research results enhance the credibility of sorghum as sustainable substrate in conventional beer brewing. This review evaluates and updates the information on progress made at various stages of conventional beer brewing with sorghum.
Keywords: sorghum; malting; mashing; malt enzymes; diastatic power; wort; beer